Скица за една неомарксистичка херменевтика - Ноневски, Вангел (Macedonian Academy of Sciences and Arts, 2018)
The purpose of the research is to give an insight into neomarxist reflections on the phenomenon of interpretation of modern art. Theodor Adorno and Walter Benjamin are taken as representatives of the Frankfurt School, who offer authentic approaches to the interpretation of modern art. In its new formal and structural features and in its new social, cultural and media reality, they anticipate that the ontology and semantics of new art requires a shift in the hermeneutic approach, from interpretation/understanding to proactive recontextualization. Fredric Jameson is taken as a factor of synthesis who, through a critical treatment of the discourses of Adorno and Benjamin, offers an authentic contextualization of neomarxist hermeneutics in a narrative context.
Sketch for a Neomarxist Hermeneutics
Keywords: hermeneutics, semantics, ontology, reproduction, reuse, recontextualization, interpretation, modern art, subversion, desire